Incremental forecaster using C–C algorithm to phase space reconstruction and broad learning network for short-term wind speed prediction - Hu, Shiting; Xu, Xuefang; Li, Mengdi; Shi, Peiming; Li, Ruixiong; Wang, Shuying (Engineering applications of artificial intelligence, 2024)
Wind power gains more and more attention from all over the world as a clean and renewable energy resource, and accurate prediction of wind speed has become a hot issue. This paper presents a novel incremental forecaster based on phase space reconstruction and broad learning network (BLN) for short-term prediction. First, time delay and embedding dimension which take an essential part in phase space reconstruction are determined by the C–C algorithm. Then, these optimal parameters are input to the BLN trained incrementally. Afterward, forecasting values are given by the output layer of BLN. Data collected from a wind farm is adopted for verifying the efficacy of this proposed model. Furthermore, five commonly used assessment indicators are applied to evaluate predictive performance of different models. Results show that the proposed model has the smallest prediction error, which performs better than the other models at one-step to three-step ahead forecasting, and this strength is attributed to address the problem of local optimum. Furthermore, the proposed model consumes less training time than the other models. Therefore, the proposed model tends to be promising for wind speed prediction of the big data era. •The proposed model is trained incrementally with adding enhancement nodes.•The inputting node number of BLN is determined by phase space reconstruction.•The C–C method is used to select the optimal parameters of phase space.